Pengaruh Beban Kerja Terhadap Kinerja Karyawan Pada PT. Alfamart - Khofifa Gobel; Usman Moonti; Agil Bahsoan (Journal of Economic and Business Education, 2023)
The research method employed a quantitative method with a total sample of 30 people. The research finding revealed that the workload affected employees’ performance. The regression coefficient obtained in this research was 57.7%, meaning that every one percent increase in workload could improve employees’ performance at PT. Alfamart in Lolak Subdistrict, Bolaang Mongondow Regency. This was also observable from the hypothesis testing, where the results of data processing indicated that the t-count value was 7.780 with a significant value of 0.000 which was higher than the t-table value of 1.701. Hence, the hypothesis about workload affected employees’ performance at PT. Alfamart in Lolak Subdistrict, Bolaang Mongondow Regency, was accepted.